Advancing Air‐ and Moisture‐Compatible s‐Block Organometallic Chemistry Using Sustainable Solvents. Issue 31 (30th June 2021) - García‐Garrido, Sergio E.; Presa Soto, Alejandro; Hevia, Eva; García‐Álvarez, Joaquín
Abstract: Challenging conventional wisdom that s‐block organometallic reagents such as Grignard or organolithiums need to be used under protecting inert atmosphere (N2 or Ar), employing dry organic solvents with a strict temperature control, this Minireview focusses on recent advances on the use of these commodity reagents while operating under air, at room temperature and in the presence of moisture. Key for the success of these approaches has been the use of the following sustainable solvents: i ) water; ii ) Deep Eutectic Solvents (DESs ); or iii ) biomass‐derived polyols (like glycerol) or ethereal solvents [ i. e ., 2‐MeTHF or cyclopentyl methyl ether ( CPME )]. The versatility of these air and moisture compatible synthetic protocols has been demonstrated for a myriad of key organic transformations, including nucleophilic additions of RLi/RMgX reagents to unsaturated organic molecules ( i. e ., ketones, imines, esters, amides or nitriles) as well as ortho‐ and lateral lithiation of aromatic substrates, Pd catalysed cross‐couplings and anionic polymerisation of styrenes. Extension of these studies to lithium amides (LiNR2 ) or phosphides (LiPPh2 ) has enabled the development of more sustainable and efficient methods for C−N and C−P bond forming processes. These unconventional s‐block metal mediated transformations have also been successfully incorporated in one‐pot tandem processes in combination with transition‐metal and organo‐catalysis. Remarkably, in some cases the conversions and chemoselectivities observed are superior to those detected in common toxic organic solvents, while working under inert atmosphere conditions with strict temperature control. The key role played by the choice of solvent in these transformations and how it can affect the constitution of the s‐block organometallic species present in solution is also discussed. Abstract : This Minireview showcases key advances on the use of polar s‐block organometallic reagents in bioinspired solvents [water, glycerol and Deep Eutectic Solvents ( DESs )], under air, at room temperature and in the presence of moisture, a trio of conditions that for decades has been considered incompatible with the manipulation of these reagents.